2018
DOI: 10.5740/jaoacint.17-0078
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approach for the Simultaneous Determination of Carbinoxamine Maleate, Pholcodine, and Ephedrine Hydrochloride Without Interference from Coloring Matter in an Antitussive Preparation Using Smart Spectrophotometric Methods

Abstract: The presence of coloring matters in syrups usually interferes with the spectrophotometric determination of active pharmaceutical ingredients. A novel approach was introduced to eliminate the interference of sunset yellow (coloring matter) in Cyrinol syrup. Smart, simple, accurate, and selective spectrophotometric methods were developed and validated for the simultaneous determination of a ternary mixture of carbinoxamine maleate, pholcodine, and ephedrine hydrochloride in syrup. Four of the applied methods use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
(35 reference statements)
0
13
0
Order By: Relevance
“…It is reported that PHL and EPH are formulated alone or with other drugs in a syrup formulation. The obtained results and those attained using a comparison method 9 (Supplementary Table S1 ) did not differ significantly (Table 5 ). Statistical evaluation of the results adopting Student's t-test and Variance Ratio F-test 50 indicated that the two approaches performed similarly regarding accuracy and precision, respectively.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…It is reported that PHL and EPH are formulated alone or with other drugs in a syrup formulation. The obtained results and those attained using a comparison method 9 (Supplementary Table S1 ) did not differ significantly (Table 5 ). Statistical evaluation of the results adopting Student's t-test and Variance Ratio F-test 50 indicated that the two approaches performed similarly regarding accuracy and precision, respectively.…”
Section: Resultsmentioning
confidence: 79%
“…Variable methods for determination of PHL have been reported including UV/Vis spectrophotometry 9 , spectrofluorimetry 10 , high-performance liquid chromatography (HPLC) 11 14 , gas chromatography (GC) 15 , chemiluminescence 16 , non-aqueous titration 17 , and electrochemistry 5 , 18 . Similarly, EPH was determined using spectrophotometric methods 19 22 , HPLC 23 25 , capillary electrophoresis 26 29 , GC 30 , 31 , LC-MS 30 , 32 , 33 , and electrochemistry 34 , 35 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, it appears to be devoid of addiction liability in man. 4 Different analytical methods were reported for the determination of pholcodine including non-aqueous titration, 5 chemiluminescence, 4,6 UV/Vis spectrophotometry, 7 capillary gas chromatography (GC), 8,9 GC-mass spectrometry (MS), 10,11 highperformance liquid chromatography (HPLC), [12][13][14][15][16] ultraperformance liquid chromatography (UPLC)-MS/MS, 17 thinlayer chromatography, 18 capillary electrophoresis (CE), 19 electrochemistry 20 and 1HNMR-pH titration. 21 The use of electrochemical sensors and especially potentiometric sensors has become greatly expanded and now occupies a large part in different applications such as pharmaceutical, environmental and biomedical analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, developing simple and accurate methods is necessary for the detection and separation of this compound from the pharmaceutical preparations for the routine control analysis. In the literature, several quantitative methods have been presented for the determination of ephedrine in pharmaceutical preparations, including titration technique, which is frequently used to determine pure ephedrine hydrochloride in tablets, aqueous and non-aqueous solutions [6], ratio spectra derivative spectrophotometric [7][8][9], differential-derivative spectroscopic methods [10,11], two dimensional-IR [12], capillary electrophoresis [13] and liquid chromatographic analysis (LC) [14,15].…”
Section: Introductionmentioning
confidence: 99%